2020
DOI: 10.3390/a13120345
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Optimization Algorithms for Text Document Clustering—A Comprehensive Analysis

Abstract: Text clustering is one of the efficient unsupervised learning techniques used to partition a huge number of text documents into a subset of clusters. In which, each cluster contains similar documents and the clusters contain dissimilar text documents. Nature-inspired optimization algorithms have been successfully used to solve various optimization problems, including text document clustering problems. In this paper, a comprehensive review is presented to show the most related nature-inspired algorithms that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 97 publications
0
29
0
Order By: Relevance
“…For instance, the score for each class is calculated based on averaging the corresponding predicted AUCs for each class. The metric is the standard evaluation method used in the Kaggle competition which can be define as in Equation (1).…”
Section: Model Fine-tuning For Toxic Comments Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the score for each class is calculated based on averaging the corresponding predicted AUCs for each class. The metric is the standard evaluation method used in the Kaggle competition which can be define as in Equation (1).…”
Section: Model Fine-tuning For Toxic Comments Classificationmentioning
confidence: 99%
“…Social media has many positive aspects, one of which is the sense of community it provides to people [1]. Social media allows people to do in a day what would usually take a lifetime to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Judith and Jayakumari [ 23 ] proposed a hybrid algorithm that includes K-means and PSO to solve the distributed document clustering problem. Abualigah et al [ 24 ] compared a few nature-inspired optimization algorithms in text document clustering and the result showed that, according to the accuracy measure and F-measure, GWO is the best performing algorithm and GA is the least performing algorithm. Rashaideh et al [ 25 ] studied the GWO algorithm in a text document clustering problem and their result shows that GWO performs better than the -hill climbing and hill-climbing algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Clustering is a technique of finding groups of similar data based on their attributes. Effective clustering of the highdimensional dataset is an important research issue in the field of data mining (L. Abualigah et al, 2020;L. M. Q. Abualigah, 2019).…”
Section: Introductionmentioning
confidence: 99%